2022
DOI: 10.1186/s13018-022-03420-x
|View full text |Cite
|
Sign up to set email alerts
|

TiRobot‑assisted versus conventional fluoroscopy-assisted percutaneous sacroiliac screw fixation for pelvic ring injuries: a meta‑analysis

Abstract: Background The TiRobot is the only robot that has been reported in the literature for posterior pelvic injuries. We aim to compare TiRobot-assisted pelvic screw fixation with the conventional fluoroscopy-assisted percutaneous sacroiliac screw fixation. Methods We conducted a meta-analysis to identify studies involving TiRobot‑assisted versus conventional percutaneous sacroiliac screw fixation for pelvic ring injuries in electronic databases, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The question surrounding the potential of robot-assisted surgery to enhance patient prognosis remains a topic of debate, as most studies have not observed discernible disparities in postoperative functional scores among patients ( 14 ). However, in this study, the robot-assisted group exhibited superior Majeed scores compared to the control group at 3 and 6 months postoperatively, plausibly attributable to the patients experiencing milder postoperative pain and shorter hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…The question surrounding the potential of robot-assisted surgery to enhance patient prognosis remains a topic of debate, as most studies have not observed discernible disparities in postoperative functional scores among patients ( 14 ). However, in this study, the robot-assisted group exhibited superior Majeed scores compared to the control group at 3 and 6 months postoperatively, plausibly attributable to the patients experiencing milder postoperative pain and shorter hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with the problems encountered in the clinical treatment of the traditional SIS technique and inspired by the advantages of the S2AIS technique, we changed the direction of screw placement and proposed a modi ed SIS placement technique, changing from the traditional posterior-anterior or horizontal direction to the anterolateral to posterior-inferior sacral wing direction of the external plate of the ilium. With the widespread use of robotic navigation devices, the number of intraoperative uoroscopies has been greatly reduced and the accuracy of screw placement has been greatly improved [22,23]. In our clinical practice, we adopted robot-assisted modi ed SIS combined with LC-II screws to treat patients with Day II CFDP, and achieved satisfactory results.…”
Section: Introductionmentioning
confidence: 99%